“Low risk” drinking guidelines as a public health measure : RARHA Delphi survey - Montonen, Marjatta (National Institute for Health and Welfare THL, 2016)
Among European countries, there is a lot of variation in the levels of drinking defined as low/high risk and in the national defitinions of “standard drink” (“unit” in the UK), a measure used to quantify the amount of alcohol consumed. This may cause confusion among consumers who encounter on the internet or on alcoholic product labels standard drink information or drinking guidelines targeted to another market. Work in RARHA aims to clarify reasons behind the variation in low risk drinking guidelines and to explore whether some degree of consensus could be achieved in this area. A Delphi survey around “low risk” drinking, carried out in two rounds in 2015, was a step towards that aim. Joint Action on Reducing Alcohol Related Harm (RARHA) brings together all EU member states as well as Iceland, Norway and Switzerland to joint work to strengthen the knowledge base for reducing alcohol related harm. RARHA is co-funded by the European Commission and by the participant countries. Most partners are expert organizations under national ministries of health.